Pengaruh Dukungan Sosial, Pengetahuan Ibu Menyusui Terhadap Perilaku Pemberian Air Susu Ibu (ASI) Eksklusif Tahun 2021 di Puskesmas Jombang Kota Cilegon - Mitsalina Durrah Judaty; Marwati Marwati; Nuria Fitri Adista (Jurnal Ventilator, 2023)
Breast milk contains various nutrients needed in the process of growth and development of infants. Exclusive breastfeeding, namely that babies are only given breast milk, without any liquid or solid food except vitamins, minerals or drugs in the form of drops or syrup until the age of 6 months. The main obstacle to achieving correct exclusive breastfeeding is the lack of proper knowledge about exclusive breastfeeding for mothers. Objective: A mother must have good knowledge of breastfeeding. The purpose of this study was to reveal the effect of social support on exclusive breastfeeding behavior, the influence of knowledge of breastfeeding mothers on exclusive breastfeeding behavior, as well as the effect of social support, knowledge of breastfeeding mothers on exclusive breastfeeding behavior. Methods: The research method used is quantitative, namely cross sectional analytic survey method. Results:The results of the analysis show that first, the direct effect of social support on exclusive breastfeeding behavior is 34.6% and the remaining 63.4% is influenced by other variables. Second, the effect of social support on the knowledge of breastfeeding mothers is 11.8%, the remaining 88.2% is influenced by other variables. Third, the effect of knowledge of breastfeeding mothers on exclusive breastfeeding behavior is 9.9% and the remaining 90.1% is influenced by other variables. Conclusion: this study is the influence of social support, knowledge of breastfeeding mothers on behavior of giving exclusive breast milk.